2021
DOI: 10.1038/s41598-021-01059-y
|View full text |Cite
|
Sign up to set email alerts
|

Short high fat diet triggers reversible and region specific effects in DCX+ hippocampal immature neurons of adolescent male mice

Abstract: Adolescence represents a crucial period for maturation of brain structures involved in cognition. Early in life unhealthy dietary patterns are associated with inferior cognitive outcomes at later ages; conversely, healthy diet is associated with better cognitive results. In this study we analyzed the effects of a short period of hypercaloric diet on newborn hippocampal doublecortin+ (DCX) immature neurons in adolescent mice. Male mice received high fat diet (HFD) or control low fat diet (LFD) from the 5th week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 85 publications
1
5
0
Order By: Relevance
“…These results indicate that a 1-week window from PN 21-28 is insufficient to impart long-lasting memory impartments, even in males. These findings align with the reversible impacts of HFD (60% kcal from fat) exposure for 1 week (PN 35-42) on hippocampal DCX + structure and BDNF expression in rats found by Chiazza et al (2021). Khazen and colleagues (2019) examined whether 1-week juvenile (PN 21-28) vs. adult (PN 60-67) consumption of a HFD (60% kcal from fat) vs. control diet (4% kcal from fat) affected HPC-dependent memory function in male Sprague Dawley rats.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results indicate that a 1-week window from PN 21-28 is insufficient to impart long-lasting memory impartments, even in males. These findings align with the reversible impacts of HFD (60% kcal from fat) exposure for 1 week (PN 35-42) on hippocampal DCX + structure and BDNF expression in rats found by Chiazza et al (2021). Khazen and colleagues (2019) examined whether 1-week juvenile (PN 21-28) vs. adult (PN 60-67) consumption of a HFD (60% kcal from fat) vs. control diet (4% kcal from fat) affected HPC-dependent memory function in male Sprague Dawley rats.…”
Section: Introductionsupporting
confidence: 86%
“…For example, sugar-enriched high-fat diet (HFD) consumption during the entire adolescent period in rats reduces hippocampal neurogenesis and impairs spatial memory (Boitard et al, 2016). That there may be critical vulnerable windows of development within the adolescent period is suggested by results showing that 1-week HFD consumption from postnatal days (PN) 35-42, which loosely corresponds to mid-adolescence, disrupts doublecortin + (DCX + ) structure and reduces brain-derived neurotrophic factor (BDNF) expression in the HPC, which are markers of newly proliferated neurons and neural plasticity, respectively (Chiazza et al, 2021). However, these changes were shown to be largely reversed with a 1-week washout on a low-fat diet (Chiazza et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In a study based on a stereological system, it was observed that chronic alcohol consumption resulted in reduced prefrontal and anterior cingulate volumes, reduced prefrontal mean neuronal volume and reduced total neuronal volume in rats [25] . Adolescent rats fed with HFD and alcohol showed astrogliosis in the granular layer of the dentate gyrus of the hippocampus and a decrease in the number of mature neuronal cells in the CA3 region [26,27] . Under the same conditions, both the area and volume of the cerebellum became smaller, alcohol consumption had the greatest effect on the cerebellar vermis and smaller cerebellar measurements were positively associated with poorer performance in cognitive performance [28] .…”
Section: Table 1: Latency Swimming Path and Speed During The Water Ma...mentioning
confidence: 99%
“…Mixed and saturated HFD-induced impairment is also associated with changes in other neuroplasticity-related factors, such as decreased BDNF [ 93 , 95 , 97 , 106 , 113 , 115 , 123 ]. The fact that acute exposure to an HFD leads to changes in BDNF levels suggests that the alterations may be a direct cause of glutamatergic synaptic dysfunction.…”
Section: High-fat Dietmentioning
confidence: 99%